Profile of albumin prescription on a surgery department of a university hospital. Issue 2 (12th March 2012) - Rodrigues, A.I.; Campelo, I.; Machado, F.; Rama, A.C.
Abstract : Background: Although the wide use of human albumin(HA), the risks and benefits of its use in clinical practice remains not conclusive. Since Surgery is the specialty that most uses HA in our hospital, it is relevant to analyse how it is used and what are the outcomes. Purpose: Evaluation of concordance of HA prescription on a surgery department(SD) with hospital general recommendations. Materials and methods: Retrospective study of six month prescription of HA from January-June 2010. Review of patient's medical record to collect prescription data from the SD. Evaluated data: number of vials (10g) prescribed and administered; plasma albumin value before treatment (ABT) and after; prescribed daily dose; treatment duration prescribed and administered; daily cost/patient and global costs; percentage of prescriptions with ABT<2.5 g/dl and percentage of prescriptions with ABT≥2.5 g/dl; justification for use. Descriptive statistics (mean±SD). Results: During six months 329 prescriptions were made to 226 patients: Number of vials prescribed: 3121 and administered: 2705 with global cost 68.950, 45€; Plasma albumin before treatment: 2.4±0.5 g/dl(1.2-5.4) and after: 3.0±0.5 g/dl(1.9-5.2); Prescribed daily dose: 27.7±6.3 g (10-60); Treatment duration- prescribed: 4.0±1.0 days (1-10) and administered: 3.0±1.2 days (1-10); Daily cost/patient: 70.6±16.1€(25.5€-152.9€); Percentage of prescriptions with ABT<2.5g/dl: 56.8%; Percentage of prescriptions with ABT≥2.5 g/dl: 41.3% – 1135 administered vials with a cost of 28.931, 15€; Justification for use: hypoalbuminaemia: 57.3%, postoperative hypoalbuminaemia: 12.4%, pathology of gastrointestinal tract: 7.0% and others: 23.3%. A percentage of 13.3 HA are not administered and return to pharmacy department. Conclusions: The authors found 41.3% of prescription profile not in accordance with hospital general recommendations – HA administration only if the ABT<2.5g/dl. The results of this pilot study, lead us to conclude that, to better support prescription, plasma albumin ought to be measured before and after treatment, and that, systematic drug utilisation review programs, should be started to assure a better cost/effectiveness ratio.